Fenomena Flexing Seleb Tiktok Adeline Margaret Sebagai Komunikasi Simbolik - Octamadian, Salza Leza; Sari, Sapta; Yanto, Yanto (Professional: Jurnal Komunikasi dan Administrasi Publik, 2024)
The Flexing phenomenon in TikTok celebs is not just a physical act of showing off wealth and based on several studies, TikTok celeb flexing is a form of symbolic communication. The purpose of this study was to determine the flexing performed by TikTok celeb Adelina Margareta as symbolic communication. This research uses a qualitative method with a semiotic analysis approach of the Roland Barthes model whose focus of attention is on the idea of two-stage signification (two orders of significations), namely analyzing the signifier and signified. Based on the results of the analysis of the 2 TikTok contents of Adeline Margaret with the Roland Barthes theoretical approach, it is known that the two contents analyzed contain denotative, connotative and mythical meanings to create audience perceptions on symbols of social status, financial success, or self-image that Adeline Margaret wants to project. The denotation of the act is a direct representation of the object shown, which is wealth. The connotation refers to the social values associated with luxury and fame. The hedonistic lifestyle and showing off luxury goods is a form of representation of the lives of the wealthy. Through her visual and narrative representations, Adeline Margaret builds an idealized self-image and inspires her followers to pursue a similar lifestyle.